Implementing Effective Leadership and Coordination Systems for Better Health Outcomes in Ethiopia (2004–2016) - BEKELLE, Engida Abebe (2019)
This case study examines how the government of Ethiopia implemented an approach for comprehensive policy planning and mechanisms for improved stakeholder coordination in the health sector. In line with this approach, the government designed an innovative policy intervention, the Health Extension Program (HEP), in 2004 as an integral part of the second Health Sector Development Program (HSDP). This intervention was believed to build efficiency and effectiveness in terms of finance mobilization and utilization and to fill skill gaps and enhance accessibility, which were the main constraining factors in the execution of the first HSDP. However, implementation faced delivery challenges including inadequate stakeholder coordination and engagement and diffuse leadership and commitment capacity among the government and stakeholders. To address these problems, the government implemented various coordination and leadership strategies to leverage the impact of overall involvement in the health sector. This included the creation of an overarching coordination mechanism led by the Joint Consultative Forum (JCF), which consists of ministers and heads of bilateral and multilateral development partners. It focuses on and discusses strategic issues every quarter. The JCF is technically supported by the Joint Core Coordinating Committee (JCCC), which includes experts from the Federal Ministry of Health (FMOH) and development partners and focuses on planning, evaluation, and auditing and reporting systems. This serves as a coordination mechanism for the Government of Ethiopia and development partners to work together effectively for better health outcomes.